PECALANG SEGARA: SATUAN TUGAS KEAMANAN TRADISIONAL PENJAGA KELESTARIAN LINGKUNGAN PANTAI DAN LAUT: STUDI KASUS DI DESA PAKRAMAN PEMUTERAN, GROKGAK, BULELENG, BALI - Atmadja, Anantawikrama Tungga (Bumi Lestari, 2013)
Abstract This article is about background of founding pecalang segara (seashore security) and its role in preserving the beach and sea environment in Desa Pakraman Pemuteran, Grokgak, Buleleng, Bali. The disccusion of this problem is done through field research, using qualitative approach that is based on critical social theory. Result of this research shows that local community preserve their ocean because of ideology, ecology, economy, and sociology reason. The role of pecalang segara is very important, such restoration and coral cultivation, control and giving sanction toward crime on seashore and ocean ecosystem. This activity needs cooperation with any party, namely desa pakraman, desa dinas, hotel owner, local government, NGO, etc.
Keywords: Keywords: pecalang segara, preservation, seashore and ocean ecosystem.